(NmOSKWA I MOSKWI^I(B: [(No^ERKI(B]; s (NsTIHOTWORENIQ(B, (N\KSPROMTY (B/ s (N~ASTX (B4s - (NgILQROWSKIJ(B, (NwLADIMIRs ((NmOSKWA(B: s (NpRAWDA(B, s, 1989)
(Nw ^ETWERTYJ TOM sO^INENIJ w(B. (Na(B. (NgILQROWSKOGO WO[LI KNIGA (B"(NmOSKWA I MOSKWI^I(B", (NSTIHOTWORENIQ I \KSPROMTY(B, (NA TAKVE WOSPOMINANIQ O PISATELE(B.s
rus
Keywords: (No^ERKI(B, (N\SSEs; (NsTIHOTWORENIQs -- (N|KSPROMTYs